2015
DOI: 10.1039/c5ob00190k
|View full text |Cite
|
Sign up to set email alerts
|

DMSO/Tf2O-mediated cross-coupling of tryptamine with substituted aniline to access C3a–N1′-linked pyrroloindoline alkaloids

Abstract: The cross-coupling of tryptamine with substituted aniline to access C3a-nitrogen-linked pyrroloindolines has been developed via the consecutive cyclization of tryptamine with DMSO/Tf2O and the substitution of 3a-pyrroloindolylthionium intermediate with aniline. The use of 2,3-dihydrotryptamine instead of aniline enabled easy access to 3a-(1-indolyl)pyrroloindoline and the concise synthesis of C3a-N1'-linked pyrroloindoline alkaloid (±)-psychotriasine was accomplished.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Lastly, we also adapted this method to develop a concise enantioselective synthesis of psychotriasine, another dimeric pyrroloindoline natural product that features an unusual C–N linkage. , Using the mesolytic cleavage conditions described above with ortho -iodoaniline as the nucleophile resulted in formation of expected N -aryl pyrroloindoline 22 in 64% yield. By adopting a strategy originally developed by Baran in his synthesis of psychotriasine, the iodoaniline was subjected to a Larock annulation with alkyne 30 to furnish the core of the natural product .…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, we also adapted this method to develop a concise enantioselective synthesis of psychotriasine, another dimeric pyrroloindoline natural product that features an unusual C–N linkage. , Using the mesolytic cleavage conditions described above with ortho -iodoaniline as the nucleophile resulted in formation of expected N -aryl pyrroloindoline 22 in 64% yield. By adopting a strategy originally developed by Baran in his synthesis of psychotriasine, the iodoaniline was subjected to a Larock annulation with alkyne 30 to furnish the core of the natural product .…”
Section: Resultsmentioning
confidence: 99%
“…Similar systems have been reported to be unstable by other researchers. 9a However when 5-bromoindoline or 5,7-dibromoindoline ( 24a ) were employed satisfactory yields were obtained (entries 8 and 9), as the bromine atoms block the undesired alkylation of the aromatic ring and slow oxidation of the indoline to the indole. Employing an indole instead of the indoline provided a complex mixture of products.…”
mentioning
confidence: 99%
“…Kawasaki and co-workers developed a thionium-reagentmediated cross-coupling reaction of tryptamine 57a with anilines to synthesize 3a-substituted pyrroloindolines 57bg (Scheme 57). 99 The screening of N-nucleophiles revealed that electron-deficient para-substituents on aniline derivatives such as p-cyano-, p-methoxycarbonyl-, and p-bromoanilines provided pyrroloindoline products in excellent yields. However, bulky N-nucleophiles and N-alkyl nucleophiles reduced the product yield of 57f, presumably due to steric hindrance.…”
Section: Review Synthesismentioning
confidence: 99%